ANALISIS INOVASI PENGEMBANGAN KURIKULUM FIQIH BERBASIS PRAKTIK DAN PEMBIASAAN DALAM MENINGKATKAN PEMAHAMAN IBADAH SISWA MADRASAH IBTIDAIYAH - Haqiah, Nur Azizatul; Muh. Wasith Achadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the development of the fiqh curriculum through a practice and habituation approach in improving students’ understanding of worship in Madrasah Ibtidaiyah. This research employed a qualitative approach with a field research design. Data were collected through in-depth interviews with fiqh teachers and the vice principal in charge of curriculum affairs. The findings reveal that the development of the fiqh curriculum is carried out through the integration of theoretical learning and continuous worship practices. The practice and habituation approach has proven effective in enhancing students’ understanding of worship across cognitive, affective, and psychomotor domains, as well as contributing to the development of students’ religious character. However, its implementation still faces several challenges, including students’ incomplete understanding and the need for consistency in habituation practices. Therefore, the practice and habituation approach can be considered a relevant strategy in developing the fiqh curriculum in Madrasah Ibtidaiyah.